Drivers of High Incidence of Urfi Marriages and the Role of Religious Affairs Office in Mitigating the Issue - Harahap, Ahmad Bahron; Akbar, Ali (Hikmah, 2025)
Secret marriages or Urfi marriages based on custom are widely known among Indonesians. This type of marriage is contrary to Law No. 1 of 1974 on Marriage and the implementation of Government Regulation No. 9 of 1975 on the Implementation of Law No. 1 of 1974. In light of this, this study aims to analyze the reality of Urfi marriages in Mahato Village, Tambusai Utara District, with a focus on the factors causing their occurrence and the role of the religious affairs office in addressing the issue. The research method used is qualitative, based on descriptive studies, with data collection techniques including observation, interviews, and document analysis. The following is the revised version. The results of the study reveal that the factor causing the high rate of Urfi marriages is the perception that a marriage certificate is not important for every married couple. However, this situation can cause difficulties for them, especially in the event of administrative problems. The religious affairs office provides education to the community, especially young people, as a preventive measure. This study supports George Homans' Social Exchange Theory, which explains that individual decisions in social relationships, including marriage, are often influenced by considerations of benefits and costs, including administrative and legal aspects of marriage.